Effective Use of Penicillin to Improve Culture Yield for Mycobacterium Tuberculosis - Rehan Anwar, Asim Fida, Madiha Mumtaz, Luqman Anwar, Ayesha Jamil (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The aim of this study to evaluate the Mycobacterium tuberculosis (MTC) sputum culture contamination and recovery between Lowenstein-Jensenmedium (LJ) contains Pencillin+LJ and free Pencillin LJ. Study design: This was a cross sectional study conducted at Khawaja Safdar Medical College, Sialkot /Allama Iqbal Memorial Hospital Sialkot for the duration of six months from September 2022 to February 2023. Methods: A total number of the participants was 140. The male and female gender were both included who suffered pulmonary tuberculosis (PTB). The sample n=140 were analyzed for culture and contamination. The sputum samples were taken in the early morning in the falcon tube and digested, decontaminated, and homogenized by Modified Petroff method. The specimen of sputum was processed on addition of Penicillin+ LJ media, and incubation was carried out at 37°C. After eight weeks, cultures were examined. The data were analyzed by SPSS 21 software. Results: The male 64.2% show greater number of cases as compared to female 36%. The suspected cases of PTB was compared with Pencillin+ LJ media and LJ media alone. 21.4% of the samples were positive mycobacterium (MTB), 79% were contaminated on LJ media while 93% were positive (MTB), and 7.1% of the samples were contaminated on LJ media without penicillin. This difference was statistically significant (p<0.005**). The grade 2+/3+ show 50% recovery by the treatment of pencillin+LJ on positive sample and 47% contaminated sample P<0.001** while graded scanty/+1 show recovery was 38%; p=0.001** with pencillin+LJ then 37% contaminated sample; p=0.002**. The difference in recovery between treatment with penicillin and without pencillin LJ was statistically significant; p<0.005. Conclusion: The contamination rate was reduced by 47% by penicillin+LJ media. Penicillin offered great alternatives for decreasing contamination in LJ alone. Penicillin should be further used as a medium supplement to enhance recovery for LJ media. Keywords: Culture media, Mycobacterium, Penicillin